Plasma membrane retrieval in neoplastic pancreatic acinar cells. - Kanwar, Y S (1983)
The dynamics of plasma membrane retrieval has been studied in the pancreatic acinar carcinoma in order to determine if neoplastic cells exhibiting a heterogeneity of cytodifferentiation states retain the capacity to interiorize and recycle plasma membrane. To this end, the plasma membranes of neoplastic pancreatic acinar cells were labeled with radioiodinated cationic ferritin (125I-CF), and the fate of the tracer was monitored by quantitative electron microscopic autoradiography. The undifferentiated granule-deficient cells of the tumor internalized membrane-bound 125I-CF and sequestered it predominantly in lysosomes. By contrast, the differentiated granule-rich cells internalized significantly more membrane-bound 125I-CF, and the tracer was localized in secretory granules and in lysosomes. The data suggest that neoplastic cells retain the capability of retrieving plasma membrane and that the dynamics of the process is correlated with the state of cytodifferentiation of the neoplastic cells.